Russia as a great power : dimensions of security under Putin - Hedenskog, Jakob, 1970- (BASEES/Routledge series on Russian and East European studies ;, 2005)
The motivation for this book is the need for a renewed analysis of Russia, which, after a period of relative weakness and instability during most ofthe 1990s, has again reappeared in world politics as a major securityplayer, claiming the status of a great power. This is partly due to the factthat, with the advent of Vladimir Putin as president, Russia gainedincreased political stability, and partly because the Russian economystarted to show steady growth. Russia made skilful use of the policywindows of opportunity that were opened to it as a consequence of theterrorist attacks in the United Sta.